AB1327 SEROLOGICAL BIOMARKERS IN PATIENTS WITH EARLY AXIAL SPONDYLOARTHRITIS: CORRELATION WITH IMAGING AND DISEASE ACTIVITY IN 24-MONTHS FOLLOW UP (ITALIAN ARM OF SPACE STUDY). (June 2019) - Lorenzin, Mariagrazia; Ortolan, Augusta; Felicetti, Mara; Polito, Pamela; Vio, Stefania; Zaninotto, Martina; Cosma, Chiara; Favero, Marta; Lacognata, Carmelo; Ramonda, Roberta
Abstract : Background: Recently studies have focused on the role of new markers to diagnose early axial spondyloarthritis (axSpA), to evaluate disease activity (DA) and to predict patients (pts) at higher risk for a worse outcome.Common biomarkers, erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) are often ineffective in assessing DA. Objectives: To evaluate biomarkers and their correlations with clinical and DA indices and imaging in pts with early axSpA. Methods: Seventy-five patients with low back pain (≥3 months, ≤2 years, onset ≤45 years) participating in the Italian arm of the SpondyloArthritis-Caught-Early SPACE study underwent a physical examination, questionnaires, laboratory tests, X-rays and MRI of the spine and sacroiliac joints (SIJ) at baseline (T0) and during a 24-months follow-up.Two expert rheumatologists formulated axSpA diagnosis and assessed fulfilment of Assessment of SpondyloArthritis International Society ASAS criteria.The DA and physical functioning were assessed using:Bath Ankylosing Spondylitis Metrology Index (BASMI);Maastricht Ankylosing enthesitis Spondilities Score (MASES); Bath Ankylosing Spondylitis Disease Activity Index (BASDAI);Bath Ankylosing Spondylitis Functional Index (BASFI);Ankylosing Spondylitis disease activity score (ASDAS);Visual Analogue Scale (VAS pain); VAS night pain;VAS disease activity;Bath Ankylosing Spondylitis Patient Global Score (BASG1); BASG2;Health Assessment Questionnaire (HAQ);ESR;serum ultrasensitive CRP(hs-CRP);matrix metalloproteinase (MMP3);interleukin (IL) IL-22, IL-17, IL-23.Positive spine and SIJ MRI images were scored independently by 2 readers using the Spondyloarthritis Research Consortium of Canada (SPARCC) method; the spine and SIJ X-rays images were scored using mSASSS and NY-criteria.After the X-rays and MRI images of all pts were read, they were classified in accordance ASAS criteria as: 21 patients classified according to axSpA imaging arm;29 patients classified according to axSpA clinical+/-imaging arm;25 patients not fulfilling ASAS criteria. Results: Significant differences were found in the prevalence of radiographic sacroiliitis, active sacroiliitis on MRI and SPARCC SIJ scores.At T0 biomarker levels were not significantly increased in any of the patient groups.It was observed instead a significant decrease of all functional and DA indices values from T0 to 24 months in the three groups: MASES (p=0.008), BASG1(p=0.02), BASG2 (p<0.0001), haq (p=0.0002), vaspain (p=0.01), vas pain night(p=0.04), vas disease activity(p=0.05), basfi(p=0.02), basdai (p<0.0001), asdas(p<0.0001).there were no differences in the serological markers values during the 2 years follow up period.the correlation of il-17 and il-23 with other indices was not significant.on the other hand significant correlations were found between il-22 and some clinical indices (basfi, basg1, haq, vas pain);between msasss and mmp3 and between msasss and hscrp (Table 1a-b ). Conclusion: Although not significantly higher in any of the three groups, IL-22, MMP3 and hsCRP values correlated with some disease activity indices and with mSASSS. ILs, MMP-3 and hsCRP values were not significantly increased in any of the study groups and were not related to radiographic SIJ involvement or to clinical and DA indices.The limitation of the study was the small numbers of the patients in the single group and the early disease stage.Further studies are needed to analyze the validity and reproducibility of these biomarkers in early axSpA. Disclosure of Interests: None declared